Isabel red wines produced from grape pre-drying and submerged cap winemaking: A phenolic and sensory approach - Machado de Castilhos, Mauricio Bonatto [UNESP]; Gomez-Alonso, Sergio; Garcia-Romero, Esteban; Del Bianchi, Vanildo Luiz [UNESP]; Hermosin-Gutierrez, Isidro (Elsevier B.V., 2017)
The aim of this work was to determine the detailed phenolic composition and sensory profile of red wines produced from Isabel grape using two alternative winemaking: grape pre-drying (IPD) and submerged cap (ISC). IPD wines were produced by the grape drying using a tray dryer at 60 degrees C and 1.1 m/s of airflow and the ISC wines were produced using stainless steel screens inside the fermentation vessel aiming at avoiding the rise of the cap due to the carbon dioxide. As expected by the thermal degradation, IPD wines presented not quantifiable concentration of anthocyanins and were described as bitter, acid, herbaceous and astringent due to their higher content of galloylated (6.94 mg/L), monomeric flavan-3-ols (49.66 mg/L) and proanthocyanidins (6.28 mg/L), which were less affected by thermal degradation. Submerged cap wines were described as colorful, pungent and persistent in mouth probably due to the anthocyanin content (2.43 mg/L) and hydroxycinnamic acid derivatives (280.5 mg/L), respectively. Submerged cap is a promising procedure because these wines presented higher yield and anthocyanin content and color intensity similar to traditional wines; pre-drying winemaking can be considered less promising since it presented lower yield and sensory features that are not very appreciated by the consumers. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Red wine; Vitis labrusca; Polyphenols; Sensory profile; Antioxidant capacity